"No turning back": The emergence and settlement of GMO hegemony in Brazil. (January 2022) - Fontoura, Yuna; Krieger, Morgana G. Martins; Peci, Alketa
Abstract: In the globalized agri-food system of the 21st century, plantations of genetically modified crops have increased considerably worldwide, justified by arguments such as food security and feeding the world's population. In Brazil, genetically modified organisms (GMOs) have indisputably consolidated as a hegemonic type of market-centered agriculture, despite continuous resistance. Therefore, the research question guiding this study is what are the discursive articulations that prompted GMO hegemony in Brazil, despite the distinctive counterhegemonic articulations shaping this field of struggle? Grounded on Laclau and Mouffe's political discourse theory (PDT) of hegemony formation, we qualitatively assess a corpus of mainstream newspaper articles and documental sources to develop a longitudinal analysis of the GMO arena. Our analysis of key periods helps elucidate GMO hegemony establishment in Brazil, comprising six articulation processes conducted by pro-GMO actors concerning anti-GMO discourses. Our paper contributes to a better understanding of how hegemonic actors in rural Brazil shaped articulation practices to establish GMO hegemony, diminishing state and media control, and fostering market-oriented arrangements. Highlights: GMOs represent a cornerstone of agro-neoliberalism in Brazil, despite resistance. This hegemony developed through discursive articulations that aim at fixing meanings. A longitudinal analysis enabled these discursive articulations to be identified. Key periods over the last decades led to the settlement of GMO hegemony. Pro-GMO actors followed a modus operandi, comprising six articulation processes.